Pregnancy in Patients with Non-cirrhotic Portal Hypertension: A Literature Review - Suprabhat Giri; Shradhanjali Sahoo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Pregnancy in non-cirrhotic portal hypertension (NCPH) is an uncommon condition. Its management is challenging both to the obstetricians as well as to the gastroenterologists due to the lack of more extensive studies and standard clinical practice guidelines. These patients are at increased risk of portal hypertension (PTH) complications, especially variceal bleeding, and with an increased incidence of adverse maternal and fetal outcomes. Hence, a multidisciplinary approach is required for management of pregnancy in NCPH. This short review describes the different aspects of pregnancy with NCPH, emphasizing specific strategies for preventing and managing PTH from the preconceptional period to postpartum.